1987
DOI: 10.1104/pp.83.4.1037
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Physical State of Membrane Lipids during Senescence of Rose Petals

Abstract: Changes in the physical state of microsomal membrane lipids during senescence of rose flower petals (Rosa hyb. L. cv Mercedes) were measured by x-ray diffraction analysis. During senescence of cut flowers held at 22°C, lipid in the ordered, gel phase appeared in the otherwise disordered, liquid-crystalline phase lipids of the membranes. This was due to an increase in the phase transition temperature of the lipids. The proportion of gel phase in the membrane lipids of 2-day-old flowers was estimated as about 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 16 publications
1
22
1
Order By: Relevance
“…This would be in line with findings for Ipomoea (2), Tradescantia (24), and rose (13) in which a decrease in the amount of phospholipid and its rate of synthesis can precede by several hours the ethylene climacteric and loss of turgor.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This would be in line with findings for Ipomoea (2), Tradescantia (24), and rose (13) in which a decrease in the amount of phospholipid and its rate of synthesis can precede by several hours the ethylene climacteric and loss of turgor.…”
Section: Discussionsupporting
confidence: 75%
“…First, there is a decrease in the amount of phospholipid in Ipomoea (2), Tradescantia (24), and rose (7), due to both reduced synthesis and enhanced degradation. Second, there is an increase in the sterol to phospholipid ratio, leading to decreased membrane fluidity in Ipomoea (2), carnation (1,26), and rose (13) and to changes in the fatty acid component of the lipids (21). In our study, we looked at relative 32p incorporation into individual phospholipids rather than at their amounts.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the accumulation of these metabolites in membranes and ensuing lipid-phase separations are well-established manifestations of senescence for a number of plant tissues (Barber and Thompson, 1983;Platt-Aloia and Thomson, 1985;Faragher et al, 1987) and have been shown to correlate temporally with impairment of blebbing (Yao et al, 1991b;Hudak et al, 1995). Particles of similar size and shape to those isolated from the cytosol are evident in the cytoplasm of intact cells in electron micrographs of thin-sectioned carnation petal tissue (Hudak and Thompson, 1996), which supports the contention that they are in situ elements of the cytosol.…”
Section: Discussionmentioning
confidence: 99%
“…In all plant tissues studied so far, aging cell membranes exhibit gradual changes in the physical properties of their component lipids, including a decrease in their fluidity (3) and an increasing proportion of lipid domains in the gel phase (6,14). These changes precede the loss in the capacity of the membranes to act as a hydrophobic barrier (6).…”
Section: Plant Materialsmentioning
confidence: 99%